3D isomorphous lanthanide coordination polymers displaying magnetic refrigeration, slow magnetic relaxation and tunable proton conduction. Issue 43 (17th October 2018) - Bera, Siba Prasad; Mondal, Arpan; Roy, Subhadip; Dey, Bijoy; Santra, Atanu; Konar, Sanjit
Abstract : Four lanthanide 3D coordination frameworks with 1D hydrophilic channels along the crystallographic c direction have been investigated for their proton conduction and magnetic properties. Abstract : Four new isostructural lanthanide-based three-dimensional (3D) coordination polymers (CPs), {[Ln4 (OH)4 (L)2 (H2 O)8 ]·4.6H2 O·1.4CH3 CN} n (Ln 3+ = Gd 3+ (1 ), Dy 3+ (2 ), Ho 3+ (3 ) and Er 3+ (4 )), have been constructed using a sulfonate–carboxylate-based ligand (Na2 H2 L = disodium-2, 2′-disulfonate-4, 4′-oxydibenzoic acid) and the corresponding lanthanide metal(iii ) nitrates. All the CPs1–4 contain [Ln4 (μ3 -OH)4 ] 8+ cubane-like cores interconnected through L 4− ligands to give rise to 3D coordination frameworks with 1D hydrophilic channels along the crystallographic c direction. From the topological perspective, the underlying 3D nets of the CPs can be classified as a 3, 6, 6-c net with an undocumented topology. Magnetic studies display that CP1 exhibits a magnetocaloric effect with a significant magnetic entropy change (−Δ S m ) = 34.6 J kg −1 K −1 for Δ H = 7 T at 3 K. CP2 shows field-induced slow magnetic relaxation properties with energy barrier ( U eff / k B ) = 30.40 K and relaxation time ( τ 0 ) = 2.47 × 10 −7 s. Theoretical calculations have been performed to corroborate the magnetic exchange coupling constant value for CP1 and to obtain a deeper understanding of the field-induced slow magnetic relaxation behavior of CP2 . Impedance analyses display high values of proton conductivity which reach 2.02 × 10 −6, 2.96 × 10 −6, 4.56 × 10 −3 and 6.59 × 10 −3 S cm −1 for CPs1–4, respectively at high temperature (>75 °C) and 95% relative humidity (RH) in the order CP1 < CP2 < CP3 < CP4 . Notably, the proton conductivities for CPs3 and4 are a few orders of magnitude higher than those of CPs1 and2 (10 −3 S cm −1 vs. 10 −6 S cm −1 ), and the conductivity increases periodically following the decreasing order of ionic radius (Gd 3+ > Dy 3+ > Ho 3+ > Er 3+ ). This demonstrates the effective employment of the lanthanide contraction strategy to tune proton conductivity while preserving proton-conducting pathways.